1991
DOI: 10.1159/000177644
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Lowering Effect of the Mushroom Pleurotus ostreatus in Hereditary Hypercholesterolemic Rats

Abstract: We studied the effect of the edible mushroom Pleurotus ostreatus (4% in diet containing 1 % of cholesterol) on serum and liver lipids in female rats with hereditary enhanced sensitivity to alimentary cholesterol. We found that the consumption of the mushroom-containing diet prevented serum cholesterol increase which was manifested at the end of the 4th week of the experiment. At the end of the 7th week of the experiment the choles-terolemia was lowered by almost 40% as compared with control animals kept on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 12 publications
0
37
0
1
Order By: Relevance
“…P. Kumm. Water and 30% ethanolic extract Antioxidant (Wang et al, 1995(Wang et al, & 1996, Hypocholesterolemic (Bobek et al, 1991(Bobek et al, & 1993 Pleurotus tuberregium (Rumph. ex Fr.)…”
Section: Flammulina Velutipes (Curtis) Singermentioning
confidence: 99%
See 1 more Smart Citation
“…P. Kumm. Water and 30% ethanolic extract Antioxidant (Wang et al, 1995(Wang et al, & 1996, Hypocholesterolemic (Bobek et al, 1991(Bobek et al, & 1993 Pleurotus tuberregium (Rumph. ex Fr.)…”
Section: Flammulina Velutipes (Curtis) Singermentioning
confidence: 99%
“…Lovastatin and its analogues are powerful inhibitors of 3-hydroxy-3-methyl-glutaryl-CoA (HMG-CoA) reductase and as such are well-known cholesterol-lowering agents (Shimada et al, 2003). It has also been found that the addition of 2 and 4% of P. ostreatus to a hyperlipidemic diet can prevent the accumulation of cholesterol and triacylglyceride in both the sera and livers of rats with exogenous, endogenous, or genetically induced hyperlipidemia (Bobek et al, 1991;Bobek et al, 1993). A reduction of the serum cholesterol level of up to 80% was also observed from the feeding of the whole mushroom, water and 30% ethanol extract of P. ostreatus to rats.…”
Section: Mushrooms As Hypocholesterolemic Agentsmentioning
confidence: 99%
“…Wild mushrooms are becoming more and more important in our diet for their nutritional (Breene, 1990;Crisan & Sands, 1978;Manzi, Gambelli, Marconi, Vivanti, & Pizzoferrato, 1999), organoleptic (Maga, 1981) and pharmacological (Bobek & Galbavy, 1999;Bobek, Ginter, Jurcovicova, & Kunia, 1991;Bobek, Ozdyn, & Kuniak, 1995) characteristics. The consumption of wild edible mushrooms is increasing due to a good content of proteins and trace minerals (Ogundana & Fagade, 1982;Senatore, 1990;Thimmel & Kluthe, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of grifolin and neogrifolin to the high cholesterol diet was found to lower plama cholesterol level significantly. Key Words Ningyotake, Polyporus confluens, mushroom, plasma choles terol, hypocholesterolemic effect Certain species of mushroom have been shown to lower plasma cholesterol level in experimental animals (1)(2)(3)(4)(5). As a hypocholesterolemic factor of Shiitake (Lentinusedodes) mushroom, eritadenine (4-(6-aminopurine-9-yl)-4-deoxy-D-eryth ronic acid) was found by several groups of investigators (6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%